Post-Combustion Carbon Dioxide Capture By Porous Carbon From Cassava Leaves In A Fixed-Bed - Md Poad, Siti Mariam (Universiti Sains Malaysia, 2018)
Porous carbon has been gaining attention in carbon dioxide (CO2) capture. Its physical and chemical characteristics can be enhance through some modifications by activating it with an activating agent. In this research, cassava leaves was used as a precursor to prepare adsorbents for CO2 capture. Cassava leaves was chosen as it is waste, easily available and cheap. The adsorbents was prepared through a series of carbonization and chemical activation steps. The surface morphology and functional groups of the prepared adsorbents were characterized by Breneur Emmett Teller (BET) surface area, Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The adsorption of CO2 was carried out in a fixed bed adsorption system with an online carbon dioxide analyzer to determine the concentration of CO2 in the outlet gas. The effect of operating conditions such as total flow rate (30-60 mL/min), adsorption temperature (30-60 °C) and CO2 concentration (10-20%) were studied. The BET surface area obtained is 1246.07 m2/g. The FTIR spectra obtained for CL@600-K2 shows more amine functional group compared to CL@600. The best adsorption capacity and breakthrough time obtained is at adsorption condition of CO2 concentration of 10%, adsorption temperature of 30 °C, total inlet flowrate of 30mL/min with 0.5 g adsorbent loading was 3.16 mmol/g and 9.83 min respectively. The highest adsorption capacity of 4.54 mmol/g was achieved at 20% of CO2 concentration. The regeneration was able to perform up to 6 cycles with a decreased of 9.46% from initial adsorption capacity. The results obtained suggest that the prepared adsorbent gave positive results on adsorption performance.